Atomic level fluxional behavior and activity of CeO2-supported Pt catalysts for CO oxidation - Joshua L. Vincent (Nature Portfolio, 2021)
In heterogeneous catalysts, the nature of the atomic-scale dynamics taking place at nanoparticle surfaces during catalysis is not understood. Here, we employ electron microscopy to show that activity directly correlates with fluxional behavior of the surface and interface atoms.